Dental treatment of children referred to general anaesthesia – association with country of origin and medical status - D. HAUBEK, M. FUGLSANG, S. POULSEN, & I. RØLLING (Paediatric Dentistry, 2006)
A small proportion of children and adolescents need dental treatment with general anaesthesia (DGA).